PENGARUH PROMOSI PENJUALAN, IKLAN DAN WORD OF MOUTH (WOM) TERHADAP MINAT BELI KONSUMEN PADA TOKO SEMOGA SUKSES CELL PEKANBARU - Nurhajat Windarsono; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to analyze Selling Promotion, Advertisement and Word of Mouth (WOM) at Store Semoga Sukses Cell Pekanbaru. Selling Promotion as a variable (X1), Advertisement as a variable (X2), Word of Mouth (WOM) as a variable (X3) and Consumer Buying Interest as a variable (Y). The method used in this study is descriptive and quantitative using the SPSS 21 program, where the sample used is 93 person. The results of the analysis use the validity test, reliability test, determination test, simple linear regression test, multiple linear regression test, t test and F test. So that it can be concluded that Selling Promotion has a significant effect on Consumer Buying Interest at Store Semoga Sukses Cell Pekanbaru, Advertisement has a significant effect on Consumer Buying Interest at Store Semoga Sukses Cell Pekanbaru and Selling Prmotion, Advertisement and Word of Mouth (WOM) has a significant effetct on Consumer Buying Interest at Store Semoga Sukses Cell Pekanbaru.Keywords : Selling Promotion, Advertisement, Word of Mouth (WOM) and Comsumer Buying Interest